Cranky Paws - Odgers, Darrel; Dawson, Janine Odgers, Sally (Scholastic Press Lindfield, N.S.W., 2008)
I'm Trump, Animal Liaison Officer at Pet Vet Clinic! It is my job to help sick animals. All the patients that come to Pet Vet Clinic are interesting, but some are more interesting than others. Take Cranky Paws the cat, for example ... Her name wasn't really Cranky Paws, but that's what Dr Jeanie and I called her. I'd never met a cat who was so determined to hate everyone!